Lepidochelys olivacea status and its relationship with nest management on the eastern coast in the Pacifico of Guatemala. - Morales-Mérida, Berta Alejandra (Instituto Tecnológico de Costa Rica, 2022)
Marine turtles are reptiles that have lived in the Earth’s oceans and nested on the beaches starting several million years ago and also have coexisted with coastal communities since humans colonized beach areas across the world. In recent decades, with increased recognition of biodiversity loss and animal extinction, scientists have focused their research on different conservations strategies for various taxa. Marine turtles, with their global distribution and widespread occurrence in various regions, have also been the focus of conservation research and planning. Marine turtles spend the majority of their lives in the oceans, except for brief periods associated with reproduction: when females emerge from the ocean to lay eggs in the sand on open beaches, and when successfully developed hatchlings emerge from their nests and scramble to the ocean. As beaches are important habitat for sea turtles, they often are protected globally, with different conservation methods, and strategies of nest protection have emerged. In Guatemala, nest depredation by people (also referred to as poaching) has been identified as a threat to sea turtles since the early 1970s. This problem has led the authorities to establish an exclusive conservation strategy that focused on protected beach enclosures called hatcheries, in which sea turtle eggs are reburied for protection and ensure a higher hatching success (CONAP, 2015). In this system, people collect eggs from freshly laid sea turtles on various beaches. The egg collectors are required to deliver a “conservation quota” of 20% of the eggs found in the nest to an officially registered hatchery. In exchange, they are allowed to keep or sell the remaining eggs for human consumption or other purposes (CONAP, 2018). This system applies only to the marine turtle Lepidochelys olivacea, considered the most abundant and constant nesting species in the Pacific of Guatemala. Commercialization of eggs of other species is illegal under federal law.
Tesis (Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión y Cultura Ambiental) Instituto Tecnológico de Costa Rica. Universidad Nacional de Costa Rica. Universidad Estatal a Distancia de Costa Rica, Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión de los Recursos Naturales, 2022.
Keywords: Biodiversidad; Tortugas marinas --- Conservación; Extinción de especies; Protección --- Nidos; Viveros --- Protección animal; Biodiversity; Sea turtles --- Conservation; Species extinction; Protection --- Nests